Improving Students' Story Telling Ability by Using Youtube Video - Yeni Afriyeni; Gunaldi Masbiran (Journal of English Language and Education, 2022)
The research objective is to describe the process and results as an effort to improve storytelling ability by using YouTube video for x grade students of MA Al-Fajar Pekanbaru. The method that used for the research is a descriptive method in the form of classroom action research (CAR). Data analysis techniques used were comparative descriptive techniques and critical analytic techniques. The results showed that the use of by using YouTube video can improve the storytelling ability for x grade students of MA Al-Fajar Pekanbaru.